JENIS MAKANAN YANG MEMPENGARUHI TERJADINYA KARIES GIGI PADA ANAK KELAS V SD NEGERI 102078 KECAMATAN BANDAR KHALIFAH KABUPATEN SERDANG BEDAGAI - S, Rosdiana Tiurlan Simaremare; Manta Rosma (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Caries tooth is disease network hard marked teeth _ with happen demineralization / dissolution of the layer outside teeth . Caries children 's teeth Still high , here caused Because consume destructive food _ health tooth ie sweet and sticky food , all- round food sour , food in the form of substance flour , hard foods , hot foods _ _ extreme and drink soft drinks For look after health his teeth . Study This aim For know connection type food to happen caries children 's teeth class V SD Negeri 102078 District . Bandar Khalifah Regency . Serdang Bedagai . As for types research used _ is study descriptive with method survey. Study done to children class V SD Negeri 102078 with population taken _ is all over child Class V of SD Negeri 102078 has 84 people and those who are sample ie whole amount population namely 84 people. Research results showing many kid who likes it consume related foods _ to damage tooth namely those who consume oranges 84.5% amount caries 9.6%, who consume pineapple 67.9% the amount of caries 9.4%, who consume water guava 55.9% amount caries 7.9%, who consume watermelon 52.4% amount caries 6.9%, who consume kedongdong 35.7% total caries 5.2%, who consume vegetables 29.8% total caries 2.9% and those who consume destructive food _ health teeth and mouth namely those who consume sweet and sticky foods 78.6% of the amount caries 10.9%, who consume all -round food acid 27.4% amount caries 4.3%, who consume food in the form of starch_73.8 % amount caries 9.8%, who consume food accounts for 60.7% of the amount caries 8.7%, who consume hot food _ extreme 77.4% amount caries 10.3%, who consume drink soft drinks 63.1% amount caries 7.9%.